Subungual Congenital Nevus with Recurrent Nevus Phenomenon. Issue 5 (7th July 2015) - El‐Khayat, Rami H.; Rashid, Abid; Walsh, Maureen Y.; McKenna, Kevin E.
Abstract Melanonychia is uncommon. We report the first case of histopathologic recurrence of a completely excised subungual congenital nevus that presented as congenital melanonychia